Ultrasensitive Aptasensors for the Detection of Viruses Based on Opto-Electrochemical Readout Systems - Divya; Dkhar, Daphika S.; Kumari, Rohini; Mahapatra, Supratim; Kumar, Rahul; Chandra, Pranjal (MDPI, 2022)
Viral infections are becoming the foremost driver of morbidity, mortality and economic loss all around the world. Treatment for diseases associated to some deadly viruses are challenging tasks, due to lack of infrastructure, finance and availability of rapid, accurate and easy-to-use detection methods or devices. The emergence of biosensors has proven to be a success in the field of diagnosis to overcome the challenges associated with traditional methods. Furthermore, the incorporation of aptamers as bio-recognition elements in the design of biosensors has paved a way towards rapid, cost-effective, and specific detection devices which are insensitive to changes in the environment. In the last decade, aptamers have emerged to be suitable and efficient biorecognition elements for the detection of different kinds of analytes, such as metal ions, small and macro molecules, and even cells. The signal generation in the detection process depends on different parameters; one such parameter is whether the labelled molecule is incorporated or not for monitoring the sensing process. Based on the labelling, biosensors are classified as label or label-free; both have their significant advantages and disadvantages. Here, we have primarily reviewed the advantages for using aptamers in the transduction system of sensing devices. Furthermore, the labelled and label-free opto-electrochemical aptasensors for the detection of various kinds of viruses have been discussed. Moreover, numerous globally developed aptasensors for the sensing of different types of viruses have been illustrated and explained in tabulated form.
This paper is submitted by the author of IIT (BHU), Varanasi
Keywords: Aptamers, Nucleotide; Biosensing Techniques; Humans; Virus Diseases; Viruses Engineering controlled terms; Biosensors; Cost effectiveness; Diagnosis; Electrochemical biosensors; Losses; Metal ions; Molecules; Viruses; graphene quantum dot; metal ion; quantum dot; unclassified drug; aptamer; Aptamers; Aptasensors; Biorecognition elements; Detection device; Detection of virus; Digital health; Human health; Label free; Ultrasensitive; Viral infections; chronoamperometry; cost effectiveness analysis; cyclic voltammetry; differential pulse voltammetry; enzyme linked immunosorbent assay; Fourier transform infrared spectroscopy; Human immunodeficiency virus; impedance spectroscopy; Influenza A virus (H1N1); Influenza A virus (H5N1); limit of detection; nanofabrication; nonhuman; pH; point of care testing; Raman spectrometry; Review; signal transduction; static electricity; surface enhanced Raman spectroscopy; virus detection; X ray diffraction; X ray photoemission spectroscopy; chemistry; genetic procedures; human; isolation and purification; procedures; virus; virus infection